CENTRES FOR DRAMA AND COMEDY – MORPHOLOGICAL PROCESSES DURING THE COVID-19 PANDEMIC (Baština, 2024)
The extraordinary COVID-19 pandemic took the world by surprise. Changes brought about by the pandemic were momentous and radical, resulting in an influx of medical terminology into the everyday vernacular. The medicalization of the language led to the emergence of pandemic-themed neologisms, with the employment of different morphological processes. The accessibility of the subject of neologisms, their collection and categorisation were facilitated through the means of the internet. The internet enabled interactivity between its users and swift dissemination of neologisms. The aim of this paper is to establish what new lexical units were created during the COVID-19 pandemic and determine whether they predominantly belong to the category of compounds as the most productive of all morphological processes, according to Plag (2002: 64). The corpus consists of tweets containing COVID-19 inspired neologisms collected from the social network formerly known as Twitter, now X. The analysis of the corpus has shown that the most productive of all morphological processes was compounding, followed by derivation, blending, analogy, conversion, clipping and abbreviation.